A new species of Cyrtodactylus (Squamata: Gekkonidae) from the karst forest of northern Laos - Schneider, Nicole; Nguyen, Truong Quang; Le, Minh Duc; Nophaseud, Liphone; Bonkowski, Michael; Ziegler, Thomas (Zootaxa, 2014)
We describe a new species of the gekkonid genus Cyrtodactylus on the basis of two specimens collected from limestone forests of Luang Prabang Province, northern Laos. Morphologically, the new species is distinguishable from its congeners by a combination of the following diagnostic characters: maximum SVL 86.1 mm; supralabials 9 or 10; infralabials 7–9; dorsal tubercles in 15 or 16 rows at midbody; ventral scale rows 34–36 at midbody; precloacal groove absent; femoral scales not distinctly enlarged; precloacal pores absent in females (unknown in males); subdigital lamellae under the fourth finger 18 or 19, under the fourth toe 18–20; subcaudals not transversally enlarged; dorsal bands white, 4 or 5 between limb insertions plus another one between hind limbs; tail banded. Based on molecular analyses, the new species is clustered in the same clade with C. wayakonei and two other species from Luang Prabang and Houaphan provinces.